PERANCANGAN KOMUNIKASI VISUAL SIGN SYSTEM SEMEN PADANG HOSPITAL - RAMADIA, Dra. Zubaidah, M.Sn., San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Semen Padang Hospital is one of the hospitals in the province of West Sumatra. Semen Padang Hospital is a private hospital class B, which is equipped with 161 beds inpatient facility. Area and building SPH fairly broad, often make it difficult for visitors to find out your location and the room was going. Sign system that has been used is not complete, no uniform or consistent and placement sign system that is not appropriate to make visitors often ignore existing sign system. It is therefore necessary sign system with the aim of supporting services in order to facilitate traffic for visitors to find the information and the way the rooms were dituju.`The process of collecting data by observation, documentation, and use the methods of data analysis 5W + 1H (what / what, who / whom, where / where, why / why, how / how).Based on this analysis, the peracangan made the sign system that is divided into four by function: (1) identification sign, (2) direction sign (3) information sign (4) regulatory sign. Media support used is the table name, name cards, id cards, stickers, stamps, a queue number, and a paper bag.Keywords: Semen Padang Hospital, Support Services, Sign System.